Low- and negative-pressure hydrocephalus in children, clinical features, treatment, prognosis and proposed mechanisms - Chen, Binghong; Zhang, Yongxiang; Jiang, Yajun; Mei, Wenzhong; Zhang, Yuanlong (Frontiers in Pediatrics, 2025)
IntroductionLow- and negative-pressure hydrocephalus (L&NPH) is not a rare clinical syndrome, often seen as a consequence of multiple cranial surgery, characterized by enlarged ventricles and paradoxically low intracranial pressure. L&NPH has also been reported in children, but only a few cases have been reported in the literature and understanding of the characteristics of L.NPH, treatment and prognosis in children is lacking.MethodsWe performed a systematic analysis of 44 pediatric patients with L&NPH described in the literature and 4 patients treated at our institution.ResultsThe results indicated that the most common cause of L&NPH in children was craniotomy. More than half of children with L&NPH had surgery prior to onset of the disease, including cerebrospinal fluid (CSF) shunt surgery or CSF drainage. Conservative treatments include postural therapy, intermittent compression of the shunt pump to drain CSF, and in a small number of patients, the adjustment of the shunt pressure is effective, but the vast majority of patients (90.91%) ultimately require a shunt device repositioning and often require more than 2 days of external CSF drainage prior to surgery. After comprehensive treatment, 77.5% of pediatric patients with L&NPH recover to pre-existing hydrocephalus, while 22.5% have severe symptoms such as coma or vegetative state or even death, which are clearly associated with the progression of the underlying disease.DiscussionThe pathophysiological mechanism may be the result of self-regulatory decompensation of CSF circulatory dynamics, brain relaxation due to excessive loss of interstitial fluid in brain tissue, and gradual increase in compliance.